A remote interactive music keyboard tuition system - Newton, Mark Brian (Rhodes University, Faculty of Science, Department of Computer Science, 2005)
A networked multimedia system to assist teaching music keyboard skills to a class is described. Teaching practical music lessons requires a large amount of interaction between the teacher and student and is thus teacher intensive. Although there is a range of computer software available for learning how to play the keyboard, these programs cannot replace the guidance of a music teacher. The possibility of combining the music applications with video conferencing technology for use in a keyboard class is discussed. An ideal system is described that incorporates the benefits of video conferencing and music applications for use in a classroom. A design of the ideal system is described and implemented. Certain design and implementation decisions are explained and the performance of the implementation examined. The system would enable a music teacher to effectively teach a music class keyboard skills.
Keywords: Computer-assisted instruction; Keyboard instrument music -- Instruction and study; Music -- Computer assisted instruction; Music in education